2009
DOI: 10.1242/dmm.000836
|View full text |Cite
|
Sign up to set email alerts
|

Foci of Listeria monocytogenes persist in the bone marrow

Abstract: SUMMARYMurine listeriosis is one of the most comprehensive and well-studied models of infection, and Listeria monocytogenes has provided seminal information regarding bacterial pathogenesis. However, many aspects of the mouse model remain poorly understood, including carrier states and chronic colonization which represent important features of the spectrum of host-pathogen interaction. Bone marrow has recently been shown to harbor L. monocytogenes, which spreads from this location to the central nervous system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…During infection, clinical symptoms of listeriosis often appear after a long incubation time (26,27), and the bacterium survives the host immune system for extended periods. Using a bio-luciferase-tagged L. monocytogenes, Hardy et al (58,59) found the bacteria were undetectable in mice for up to 15 days prior spreading to gallbladder, bone marrow, etc., and they suggested that the persisting bacteria were dormant during this period (59). L. monocytogenes enters the host by crossing the gastrointestinal barrier, and it quickly translocate to the spleen and liver, where it grows intracellularly in macrophages (25).…”
Section: Discussionmentioning
confidence: 99%
“…During infection, clinical symptoms of listeriosis often appear after a long incubation time (26,27), and the bacterium survives the host immune system for extended periods. Using a bio-luciferase-tagged L. monocytogenes, Hardy et al (58,59) found the bacteria were undetectable in mice for up to 15 days prior spreading to gallbladder, bone marrow, etc., and they suggested that the persisting bacteria were dormant during this period (59). L. monocytogenes enters the host by crossing the gastrointestinal barrier, and it quickly translocate to the spleen and liver, where it grows intracellularly in macrophages (25).…”
Section: Discussionmentioning
confidence: 99%
“…9,37,38 Considering the previous reports where augmented tumor infiltration of macrophages has been correlated to an elevated myelopoietic differentiation of BMC, 10,39 we next checked if Listeria infection could alter the process of differentiation of macrophages from precursor BMC in a tumor-bearing host. Indeed, the results of the present study demonstrate an augmented bone marrow cellularity, improved BMC survival accompanied by an inhibition of proapoptotic PUMA expression, and enhanced macrophage colony-forming ability.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Thus, one of the targets of tumor immunotherapy is to usher repolarization of TAM to M1 subtype. 7,8 Reports also indicate that after Listerial infection, the bacterial load is significantly high in vital organ systems including bone marrow, 9 which is involved in differentiation of macrophages. Nevertheless, evidences suggest that bone marrow myelopoiesis is one of the important sources of TAM.…”
mentioning
confidence: 99%
“…BLI allows spatiotemporal identification of infectious foci in living hosts (Contag et al, 1995; Doyle et al, 2004). This technique allows us to decisively indicate the presence of metabolically active bacteria in deep tissues of mice (Hardy et al, 2009). …”
Section: Introductionmentioning
confidence: 99%